A comparative safety review of histone deacetylase inhibitors for the treatment of myeloma. Issue 7 (3rd July 2019) - Cengiz Seval, Guldane; Beksac, Meral
ABSTRACT: Introduction : Dysregulation of histone deacetylase (HDAC) activity is an epigenetic hallmark of multiple myeloma (MM), leading to aberrant gene expression and cellular signaling in myeloma cell growth, survival and resistance to therapy. Hyper-methylation at diagnosis is a frequent observation, which eventually may convert to hypo-methylation during advanced phases. Areas covered : A literature search on 'HDAC inhibitors' and 'multiple myeloma' was carried out using PubMed and Google Scholar in the preparation of this overview on clinical efficacy and safety data. Expert opinion : First-generation non-selective HDAC inhibitors have demonstrated minimal single-agent activity in refractory MM. Subsequently, combination therapy has proven an improvement in progression-free survival (PFS) but not response rates. The main concerns are associated with toxicities. Ongoing studies on new and more selective agents, i.e. Romidepsin or Ricolinostat, are promising in terms of better efficacy and less toxicity.